Job Demands Resources dalam Konteks Lokal: Peran Spesifik Disiplin dan Kompensasi sebagai Sumber Daya Penyeimbang - Kartika Septiary Pratiwi Musa (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
This study aims to determine the effect of workload, discipline, and compensation on employee job satisfaction at PT. Kinarya Utama Teknik Makassar This type of research is associative which aims to determine the effect between two or more variables. The data collection method used a questionnaire with 70 permanent employees as respondents. The analytical tool used is multiple linear regression (SPSS version 26). The results showed that there was a significant influence of workload, discipline, and compensation on the job satisfaction of employees of PT. Kinarya Utama Teknik Makassar